The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/imr.12788
|View full text |Cite
|
Sign up to set email alerts
|

The TCR is an allosterically regulated macromolecular machinery changing its conformation while working

Abstract: The αβ T‐cell receptor (TCR) is a multiprotein complex controlling the activation of T cells. Although the structure of the complete TCR is not known, cumulative evidence supports that the TCR cycles between different conformational states that are promoted either by thermal motion or by force. These structural transitions determine whether the TCR engages intracellular effectors or not, regulating TCR phosphorylation and signaling. As for other membrane receptors, ligand binding selects and stabilizes the TCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 140 publications
(383 reference statements)
2
40
0
Order By: Relevance
“…A possible scenario might be that ligand induces transient reorientation of the TCR α/β relative to its associated CD3 subunits in their TM helices, thus enabling changes in the intracellular tails of CD3 for phosphorylation. This would agree with the notion that the TCR-CD3 complex cycles between different conformations during action (Schamel et al, 2019). Capturing of such changes, however, may not be easily amenable to structural approaches due to their transient nature.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…A possible scenario might be that ligand induces transient reorientation of the TCR α/β relative to its associated CD3 subunits in their TM helices, thus enabling changes in the intracellular tails of CD3 for phosphorylation. This would agree with the notion that the TCR-CD3 complex cycles between different conformations during action (Schamel et al, 2019). Capturing of such changes, however, may not be easily amenable to structural approaches due to their transient nature.…”
supporting
confidence: 87%
“…The assembly of the TM segment of the TCR-CD3 complex can be compared to piston (formed by the two TM helices of TCRα/β) in cylinder (formed by the six TM helices of CD3). This seemingly agrees with the mechanical force-based models on TCR triggering (Schamel et al, 2019;Ma et al, 2007). However, piston-like movement of the two TM helices as proposed in the mechanosensor models would result in disruption of the functionally important ionic interactions formed within the TM segment of the complex (Call et al, 2002).…”
supporting
confidence: 87%
See 2 more Smart Citations
“…A major group of TCR triggering models involves conformational changes. Whereas extensive crystallographic studies have not revealed sufficient amount of conformational changes in the ectodomains of the TCR-pMHC complex [90,91], convincing evidence indicates the occurrence of conformational changes in the CD3 cytoplasmic tails, which are released from the inner leaflet of the plasma membrane accompanying TCR triggering [97,98]. Force-induced conformational change has been suggested as a mechanism TCR triggering [99,100], e.g., by inducing apposition of the CD3ζζ subunits that are spread before TCR-pMHC binding [101] and/or segmenting the bipartite helix in the transmembrane domain of the TCR α-subunit to alter its association with the CD3 subunits [102], which may dislodge the CD3 tails from the plasma membrane.…”
Section: Peripheral T Cell Homeostasis and Activationmentioning
confidence: 99%